AVT and Agency: Revoicing to Give a Voice to Minoritized Language Communities - De Ridder, Reglindis (Journal of Audiovisual Translation, 2024)
At the 10th Media for All conference, the meagre representation of minoritized languages (including sign language) in audiovisual media on streaming platforms was tackled. In this way, the very ideal of media for all was challenged. Global streaming platforms tend to adopt a ‘one size fits all’ approach in limiting their language settings to a minimum. While the users of minoritized languages often are proficient in the dominant language of their country, it is absolutely crucial that content is available in their smaller — and often endangered — languages as well. Some streaming platforms of local public service broadcasters try to accommodate this need. Still, the questions remain: to what extent do not only minoritized languages users, but also the speakers of the majority languages encounter these minoritized languages in audiovisual content, how linguistically diverse and inclusive is this content, but also: what role can audiovisual translation play here? In this article, the importance of audiovisual translation in and out of minoritized languages, with a special focus on revoicing, is discussed. The children’s content broadcast by Swedish public service broadcaster in the national minority languages and sign language is used as a case study. Lay summary People who speak less common languages or use sign language cannot always access audiovisual media in these languages. The reason for this is that the content, but also the language settings offered by streaming platforms often tend to be rather limited in this regard. For minoritised language communities, however, it is important that audiovisual media is available in their languages, as it can help safeguard these often endangered languages. Likewise, it is important that majority language users become more aware of these languages through audiovisual media. This article explores how streaming platforms can become more inclusive and also provide content in such minoritized languages for both the minoritised and majority language communities. The children’s programmes of Swedish public broadcasters that offer content in minoritised languages for both the majority language, Swedish speaking community, and the minoritised language communities are analysed and discussed as a case study. Yet, it looks at the agency of individuals who try to make a difference. The focus is on (partial) revoicing, yet (partial) subtitling and sign language interpreting are also discussed.